Numerical simulation of frontal polymerization - Dumont, Thierry (Computer Assisted Methods in Engineering and Science, 2000)
Frontal polymerization has been studied for many years experimentally and theoretically. This technique can exhibit a phase change between a liquid monomer and a solid polymer and many studies, both theoretical and experimental, have been devoted to the stability of the front which separates the two phases in the presence of thermal convection. We present here a new technique for the numerical simulation of this process which takes account of the chemical reaction, the phase transition and the hydrodynamics; it is based on the method of characteristics and a fictitious domain method. These two methods are known, but the coupling of them and the application to this problem is new. We also present and discuss some results of simulations.